A Grammatical and Theological Analysis of the Hitpael Form and the Tree Identification in Genesis 3:8 - Isak Suria; David Ming (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2026)
This article examines the theological significance of the reflexive verb form hitpael in Genesis 3:8 and investigates the identity of the tree mentioned as Adam and Eve’s hiding place. The study explores how grammatical structures and narrative elements reflect the spiritual condition of fallen humanity. Employing qualitative methods that combine grammatical and narrative analysis of the Hebrew text, the study finds that the hitpael form in vayyithabba' denotes a deliberate, self-directed action motivated by shame and alienation. The singular use of the word